(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
Based on the theoretical frameworks of situational crisis communication theory (SCCT) and person-centered messages (PCMs), this interdisciplinary study conducted a 2 x 3 experiment to examine the role of PCMs in crisis management on social media. Our findings suggest that crisis type (victim, preventable) has an effect on people’s perceptions/reactions toward an organization and that PCM levels (low, medium, and high person-centered messages) in crisis communication on social media influence organizational reputation and participants’ intention to post negative feedback about the organization in crisis. We suggest that when organizations are responding to crisis online, they provide additional attention to the interpersonal dynamics of those interactions. Theoretical and practical implications are discussed.